Pengaruh Penerapan Gaya Mengajar Komando terhadap Peningkatan Kemampuan Passing Menggunakan Kaki Bagian Dalam pada Sepak Bola Siswa di SMP Negeri 6 Tondano - Hermawan Pratama Sakka; JJ Mangindaan; Jan Lengkong (STIKES Columbia Asia Medan, 2024)
This study aims to examine the effect of applying the command teaching style on the ability to kick the ball in soccer among students at SMP Negeri 6 Tondano. The research question is whether the command teaching style can enhance the ability to kick the ball. This experimental study uses a